Factors associated with older people's emergency department attendance towards the end of life: a systematic review. (26th November 2018) - Bone, Anna E; Evans, Catherine J; Etkind, Simon N; Sleeman, Katherine E; Gomes, Barbara; Aldridge, Melissa; Keep, Jeff; Verne, Julia; Higginson, Irene J
Abstract: Background: Emergency department (ED) attendance for older people towards the end of life is common and increasing, despite most preferring home-based care. We aimed to review the factors associated with older people's ED attendance towards the end of life. Methods: Systematic review using Medline, Embase, PsychINFO, CINAHL and Web of Science from inception to March 2017. Included studies quantitatively examined factors associated with ED attendance for people aged ≥65 years within the last year of life. We assessed study quality using the QualSyst tool and determined evidence strength based on quality, quantity and consistency. We narratively synthesized the quantitative findings. Results: Of 3824 publications identified, 21 were included, combining data from 1 565 187 participants. 17/21 studies were from the USA and 19/21 used routinely collected data. We identified 47 factors and 21 were included in the final model. We found high strength evidence for associations between ED attendance and palliative/hospice care (adjusted effect estimate range: 0.1–0.94); non-white ethnicity (1.03–2.16); male gender (1.04–1.83, except 0.70 in one sub-sample) and rural areas (0.98–1.79). The final model included socio-demographic, illness and service factors, with largest effect sizes for service factors. Conclusions: In this synthesis, receiving palliative care was associated with lower ED attendance in the last year of life for older adults. This has implications for service models for older people nearing the end of life. However, there is limited evidence from European countries and none from low or middle-income countries, which warrants further research.